2015
DOI: 10.1016/j.freeradbiomed.2015.04.012
|View full text |Cite
|
Sign up to set email alerts
|

The superoxide dismutase 1 3′UTR maintains high expression of the SOD1 gene in cancer cells: The involvement of the RNA-binding protein AUF-1

Abstract: Superoxide dismutase 1 (SOD1) is the ubiquitously expressed and predominant dismutase in the cytoplasm. While transcriptional regulation of the SOD1 gene has been well characterized, post-transcriptional regulation of the gene remains largely unknown in eukaryotes. In this study, a full-length 3’UTR of the SOD1 transcript was cloned and characterized for its ability to regulate SOD1 gene expression in human cancer cells. Inclusion of the SOD1 3’UTR in the pGL3 reporter construct dramatically enhanced the repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Afonso et al (2006) identified TNF-α as a transcription factor that inhibits SOD1 transcription, translation, and promoter activity through binding to a proximal promoter sequence 157 bp upstream of the SOD1 transcription initiation site. Moreover, AUF-1 was shown to bind to the SOD1 3 UTR and primarily promotes SOD1 protein translation, leading to increased SOD1 protein expression (Zhang et al, 2015). Other mechanisms also regulate SOD1, including oxidative stress and phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Afonso et al (2006) identified TNF-α as a transcription factor that inhibits SOD1 transcription, translation, and promoter activity through binding to a proximal promoter sequence 157 bp upstream of the SOD1 transcription initiation site. Moreover, AUF-1 was shown to bind to the SOD1 3 UTR and primarily promotes SOD1 protein translation, leading to increased SOD1 protein expression (Zhang et al, 2015). Other mechanisms also regulate SOD1, including oxidative stress and phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…SOD is able to convert the superoxide (O 2 − ) radical into either oxygen (O 2 ) or the less reactive hydrogen peroxide (H 2 O 2 ) which can then be removed by CAT, GPx, or TPx. Among the three major families of SOD, those we single out in humans are the copper and zinc (Cu-Zn) SOD1, whose localization is in cytosol, nucleus, peroxisome, and intermembrane space of the mitochondria [ 114 ], the mitochondrial enzyme manganese SOD2 (MnSOD), and the (Cu-Zn) extracellular SOD3. SOD enzymes are able to exert a strong antioxidant activity.…”
Section: Thioredoxin Glutathione Peroxidase and Superoxide Dismumentioning
confidence: 99%
“…It has also been labeled as body's natural cancer fighter [23]. SOD1 however has been only recently been proposed as a novel target for cancer therapy [24] and its role in cancer is also being revealed [25]. More recently being elucidated is the role of AMD1 in cancer which has been found to be upregulated in human prostate cancer [26].…”
Section: Resultsmentioning
confidence: 99%